A State-of-the-Art Compact Surface Drifter Reveals Pathways of Floating Marine Litter in the German Bight - Meyerjürgens, Jens; Badewien, Thomas H.; Garaba, Shungudzemwoyo P.; Wolff, Jörg-Olaf; Zielinski, Oliver (Frontiers in Marine Science, 2019)
Lagrangian observations are important for the understanding of complex transport patterns of floating macroscopic litter items at the ocean surface. Satellite-tracked drifters and numerical models are an important source of information relevant to transport processes as well as distribution patterns of floating marine litter (FML) on a regional to global scale. Sub-mesoscale processes in coastal and estuarine systems have an enormous impact on pathways and accumulation zones of FML and are yet to be fully understood. Here we present a state-of-the-art, low-cost and robust design of a satellite-tracked low-cost drifter applicable in studying complex pathways and sub-mesoscale dynamics of floating litter in tidally influenced coastal and estuarine systems. It is compact, lightweight less than 5 kg, capable of refloating, easily recovered and modified. The drifter motion resolves currents of the ocean surface layer (top 0.5 m layer) taking into account wind induced motions. We further showcase findings from seven of our custom-made drifters deployed from RV Heincke and RV Senckenberg in the German Bight during spring and autumn 2017. Drifter velocities were computed from high resolved drifter position data and compared to local wind field observations. It was noted that the net transport of the drifters in areas far away from the coast was dominated by wind-driven surface currents, 1 % of the wind speed, whereas the transport pattern in coastal areas was mainly overshadowed by local small-scale processes like tidal jet currents, interactions with a complex shoreline and fronts generated by riverine freshwater plumes.